2010
DOI: 10.1210/jc.2010-0296
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Leptin Level Is a Surrogate Measure of Insulin Sensitivity

Abstract: Insulin sensitivity explains about 40% of the variance in fasting leptin levels. Thus, fasting plasma leptin levels probably serve as an endogenous response to ambient insulin resistance and may provide a surrogate measure of insulin action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
1
27
1
2
Order By: Relevance
“…Leptin infusion has been shown to ameliorate insulin sensitivity in the skeletal muscle (42), whereas insulin infusion has been shown to increase leptin levels (43), even in physiologic amounts (44). Therefore, it has been suggested that the onset of IR could lead to an increase in leptin secretion as a compensatory response (45), which might explain our findings. Indeed, we observed that insulin sensitivity estimates (fasting insulin, insulin-to-glucose ratio, Matsuda index, AUC insulin , AUC insulin/glucose , and HOMA IR) were moderately and significantly correlated with surrogate markers of inflammation CRP level and leptin, which advocates for a role of inflammation in IR in SLE.…”
mentioning
confidence: 63%
“…Leptin infusion has been shown to ameliorate insulin sensitivity in the skeletal muscle (42), whereas insulin infusion has been shown to increase leptin levels (43), even in physiologic amounts (44). Therefore, it has been suggested that the onset of IR could lead to an increase in leptin secretion as a compensatory response (45), which might explain our findings. Indeed, we observed that insulin sensitivity estimates (fasting insulin, insulin-to-glucose ratio, Matsuda index, AUC insulin , AUC insulin/glucose , and HOMA IR) were moderately and significantly correlated with surrogate markers of inflammation CRP level and leptin, which advocates for a role of inflammation in IR in SLE.…”
mentioning
confidence: 63%
“…32,33 Outside of pregnancy, serum leptin levels are positively correlated with BMI and body fat mass. 34,35 Many studies have investigated the relationship between maternal obesity and circulating leptin levels using plasma or serum samples collected at different gestational ages. 22,23,27,36,37 Although these studies are very heterogeneous and cannot be directly compared, all of them report that overweight women have significantly higher circulating levels of leptin than normal weight women, throughout pregnancy.…”
Section: Leptinmentioning
confidence: 99%
“…Adiponectin/leptin ratio may provide a reliable measure of insulin sensitivity [47]. A high carbohydrate diet promotes glucose intolerance and insulin secretion as well as reduces insulin sensitivity, therefore, increases leptin, an insulinresistance surrogate, and reduces adiponectin, an insulin sensitivity surrogate [46,48,49]. A higher consumption of carbohydrate has been found to augment leptin level [44], which is in agreement with the positive association between serum leptin level and energy percent from carbohydrates that has been detected in this study.…”
Section: Discussionmentioning
confidence: 99%